Calculation of temperature distribution in multilayer structure of embryo - Левкин, Дмитрий Артурович (Eastern-European Journal of Enterprise Technologies, 2013)
An embryo is a non-linear, non-stationary microbiological object consisting of three layers. In the chemical composition, its layers consist of protein and water. The interaction of the laser radiation with an embryo causes a nonuniform heating of the embryo, which leads to an injure of the blastomeres. To reduce the injure of the blastomeres during the interaction of the laser radiation with the embryo, it is necessary to set the numerical values of the coefficients of thermal conductivity of the layers of the embryo, and the boundary conditions of the temperature distribution in the multilayer structure of the embryo at the stage of construction of a mathematical model of interaction. The method of conductometry permitted to receive the specific conductivity of the layers of the embryo. Applying Wiedemann-Franz law, we have obtained the numerical values of the coefficients of thermal conductivity of the layers of the embryo from the coefficients of electroconductivity of its layers. The mathematical calculation of the temperature distribution in the embryo according to the spatial and temporal coordinate were conducted applying Bezier curve and irregular grid. At the stage of the construction of the mathematical model of the interaction of the laser radiation with the embryo, the definition of the numerical values of the coefficients of thermal conductivity of its layers and the boundary conditions of the temperature distribution over the layers of the embryo will reduce the injure of the blastomeres during the interaction of the laser radiation with the embryo.